The Relationship between Milking Hygiene and Salmonella sp. Contamination on Cow’s Milk in Jember Regency - Mufida, Diana Chusna; Shabri, Hammam Arif; Hermansyah, Bagus; Shodikin, M Ali; Suswati, Enny (BKM Public Health and Community Medicine, 2024)
Purpose: Milk is a liquid produced by the mammary glands of female mammals. The nutritional content of milk almost covers the entire nutritional needs required by living things. The appearance of Salmonella sp. in cow's milk is due to milking methods that do not meet the standards, especially regarding milking hygiene management. This study examines the relationship between milking hygiene and Salmonella sp. contamination in cow's milk in Jember Regency. Method: This study used observational analytic research with a cross-sectional research design. Primary data were obtained through direct observation of milkers using a checklist related to milking. observe Salmonella sp. contamination using culture techniques on SCA (Salmonella Chromogenic Agar) as selective media agar for Salmonella sp. and Gram staining. Results: The results from this study show that the hygiene process pre-milking (78.9%), during-milking (71.1%), and post-milking (89.5%) have been implemented. The statistical test results showed a relationship between the pre-milking hygiene process with Salmonella sp. contamination (p-value < 0.05), but insignificant results were seen in the during and post-milking hygiene processes (p-value> 0.05). Conclusion: The conclusion from this study show that the three results only the hygiene processes pre-milking have results associated with Salmonella sp. contamination in cows' milk. Therefore, milkers are expected to maintain and improve dairy hygiene measures, especially before milking to prevent contamination of cow's milk.